Jiawei Kongsheng Zhenzhong Pill: marker compounds, absorption into the serum (rat), and Q-markers identified by UPLC-Q-TOF-MS/MS - Wu, Qiaolan; Ou, Chunxue; Wang, Jiayun; Wu, Xiaolin; Gao, Zu; Zhao, Yue; Lu, Guangying; Wu, Zhichun; Yu, Huayun (Frontiers in Pharmacology, 2024)
Background: Jiawei Kongsheng Zhenzhong Pill (JKZP), a Chinese herbal prescription comprised of eight Chinese crude drugs, has been historically employed to treat neurological and psychological disorders. Nevertheless, the ambiguous material basis severely hindered its progress and application. Purpose: The current study aimed to establish a rapid analytical method for identifying the chemical components of JKZP aqueous extract, and the components absorbed into the rat serum to investigate the quality markers (Q-markers) responsible for the neuroprotective effects of JKZP. Methods: The qualitative detection of the chemical components, prototype components, and metabolites of the aqueous extracts of JKZP, as well as the serum samples of rats administered the drug, was performed using Ultra-performance liquid chromatography-quadrupole-time of flight tandem mass spectrometry (UPLC-Q-TOF-MS/MS) technology. This analysis combined information from literature reports and database comparisons. Moreover, the study was conducted to anticipate the potential Q-markers for the neuroprotective effects of JKZP based on the ‘five principles’ of Q-marker determination. Results: A total of 67 compounds and 111 serum components (comprising 33 prototypes and 78 metabolites) were detected and identified. Combining the principles of quality transmission and traceability, compound compatibility environment, component specificity, effectiveness, and measurability, the study predicted that five key compounds, including senkyunolide H, Danshensu, echinacoside, loganin, and 3,6’-disinapoyl sucrose may serve as potential pharmacological bases for the neuroprotective effects of JKZP. Conclusion: To summarize, the UPLC-Q-TOF-MS/MS technique could be employed to rapidly and accurately identify compounds in JKZP. Five active compounds have been predicted to be the Q-markers for the neuroprotective effects of JKZP. This discovery serves as a reference for improving quality, advancing further research and development, and utilizing Chinese herbal prescriptions.